PROJECT BASED LEARNING DALAM PEMBELAJARAN PANCASILA PADA MATERI KERAGAMAN BUDAYA SEBAGAI UPAYA MENUMBUHKAN SIKAP MENGHARGAI KEBERAGAMAN SISWA KELAS V MI MANBAIL FUTUH JENU TUBAN - Kamilah, Arina; Nada Kriswahyuni, Dia; Fatimatuz Zahro', Siti; Dhurrotul Ainiyah, Ziana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted based on the problem of low student engagement and limited appreciation of cultural diversity in Civic Education (Pendidikan Pancasila) learning in Grade V of elementary school. The study aimed to analyze the implementation of the Project Based Learning (PjBL) model in teaching cultural diversity material and to examine its impact on students’ understanding and attitudes toward diversity. This research employed a qualitative descriptive approach with data collected through classroom observations, interviews, and documentation. The learning process was carried out through project stages, including planning, implementation, and evaluation, where students worked in heterogeneous groups to create a “Mini Exhibition of Indonesian Cultural Diversity.” The findings revealed that the implementation of PjBL increased students’ active participation, collaboration, and responsibility during the learning process. Cognitively, students demonstrated better understanding of various elements of Indonesian culture. Affectively, students showed improved tolerance, respect for differences, and a stronger sense of national pride. Socially, the project activities enhanced communication skills and teamwork among students. Therefore, the study concludes that Project Based Learning is an effective and meaningful approach to foster students’ understanding and appreciation of cultural diversity in elementary Civic Education.